(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
As there is no effective treatment for kidney stones, the development and progression of renal calculi continue to be a cause for concern despite developments in contemporary medicine. In the current study, the anti-urolithiasis activity of Bougainvillea spectabilis Willd. against sodium oxalate (NaOx)-induced urolithiasis in rats was studied. Leaves of B. spectabilis were extracted with various solvents, i.e., petroleum ether, chloroform, ethyl acetate, ethanol, and water. Albino wistar male rats were divided into five groups of six animals each. All groups except the positive control were treated intraperitoneally with sodium oxalate (70 mg/kg) for 10 days. Treatment with the standard drug cystone (5 mL/kg), ethanol, and aqueous extracts (200 mg/kg) was given to the respective groups for 10 days of study. On the 10th day, serum creatinine, calcium, uric acid, blood urea nitrogen, urine calcium, oxalate, and uric acid levels were estimated, along with urine microscopy to confirm crystals. Kidneys were isolated and used for histopathological studies. The results suggested that the administration of B. spectabilis to rats with sodium oxalate-induced lithiasis reduced and prevented the formation of urinary stones. Also, the treatment of lithiasis-induced rats with the toxic control drug and extracts of B. spectabilis restored all the elevated urine and serum biochemical parameters, including creatinine, calcium, oxalate, uric acid, and blood urea nitrogen, and significantly increased the urine volume. The histopathology showed depositions of a large number of calcium oxalate crystals in the kidney in the calculi-induced group with enlargement of glomeruli and necrosis of tubules, while in the standard and extract-treated groups, small and fewer deposits were seen with the recovered architecture of the kidney tubules. The result indicates the anti-urolithiasis activity of B. spectabilis mediated possibly by the presence of flavonoids, calcium oxalate crystal inhibitors, and antioxidant properties which maintain the balance between stone promoters and inhibitors constituents and this study rationalized its medicinal use in urolithiasis.